CHARACTERIZATION AND SCREENING OF SALINITY TOLERANT POTASSIUM SOLUBILIZING BACTERIA - CH. V. DURGA RANI, BIYYANI SUMAN, S. TRIVENI, P. C. LATHA, M. SRILATHA and (The Journal of Research, PJTSAU, 2019)
Salinity stress is one of the major abiotic threats to plant life and agriculture worldwide and significantly reduces crop yield in affected areas. Excessive salinity limits plant growth and productivity and can lead to plant death. Soil salinity in arid regions is frequently an important limiting factor for cultivating agricultural crops. Potassium deficiency frequently compounds the problems of saline soil. Salt tolerant Potassium Solubilizing Bacteria (KSB) reduced the impact of salinity on plant growth and improved productivity by solubilizing unavailable potassium in the soil. In the present study native KSB was isolated from saline soils of Telangana, and the isolates were culturally, morphologically and biochemically characterizated of which 4 were identified as Bacillus sp., 3 as Pseudomonas sp. and 2 as Azotobacter sp.according to the Bergey’s manual of systemic bacteriology. The isolates were screened for ACC deaminase activity, EPS production and PGP attributes like siderophore production, HCN and IAA production. Out of 9 isolates, 4 produced ACC deaminase, 6 isolates produced exopolysaccharides 4 produced HCN and 6 isolates showed positive for IAA production and only 2 isolates produced siderophores.